Disabled skiing
Homepage of the World Cup Committee for alpine skiing for disabled. Contents: The World Cup Committee The Committee's Duties The Committee's Vision The Managment of the World Cup Committee Participating Nations List of patrons Alpine Skiing for the Disabled (The Events, The Categories in Alpine Skiing for the Disabled, The Classifications, The Handicap System, The FIS Rules and the Allowances for the Disabled ) Background Information (The History of Alpine Skiing for the Disabled, The Importance of Competitions for the Disabled, the Problems Faced, Abbreviations/ Glossary) Addresses (World Cup Committee, FIS-Alpine-Committee, IPC-Alpine-Committee) Nordic Skiing for the Disabled Addresses National associations for Disabled